Static Pressure of Sea Ice (Statischeskoe Davlenie Morskogo l'da) - Peschanskii,I. S. (1973)
Static pressure in ice develops in an ice cover on sudden rise in the temperature. At this time, the ice expands, exerting pressure on the shore belt and the engineering structures located there. The more abruptly this occurs, the higher the pressure. This static pressure of sea ice depends not only on the value of temperature drop and speed of its effect, but also on the salinity of the ice and on its ultimate temperature. The effects of these changes in temperature, its speed and the salinity in sea ice and freshwater ice (and the differences between the two types of ice) is discussed as well as the pressure distribution through the ice's thickness. (Author) Draft trans. of Arkticheskii i Antarkticheskii Nauchno-Issledovatelskii Institut. Trudy (USSR) v300 p4-8 1971.